(untitled) (Texas Journal of Engineering and Technology, 2022)
On September 15, 2006, ISO/IEC 17021:2006 Conformity assessment -Requirements for bodies providing audit and certification of management systems In December, on the eve of 2007, the International Accreditation Forum (IAF) and the International Organization for Standardization (ISO) issued a joint communiqué establishing a global two-year transition period for meeting its requirements until September 15, 2008.